Effect of propylene glycol on fertility of postpartum dairy cows experiencing seasonal heat stress - Yildiz, Atilla; Erisir, Zeki (Agricultural Research Communication Centre, 2016)
The objective of this study was to evahiate effects of a daily oral drench of Propylene Glycol (PG) on fertility in dairy cows experiencing seasonal heat stress. In treatment group, cows (n=9) were treated with, drenching 250 ml propylene glycol once daily from 3 to 15 days post-partum following the morning milking. Another group of cows (n=9) was selected as untreated control. The serum beta-hydroxybutyrate (BHBA) concentrations were used as indicators of energy status of the cows. Days to onset of luteal activity, calving to first service interval and pregnancy rate to first service were used to evaluate the reproductive performance. There was no difference in onset of luteal activity postpartum between the treatment and control groups. But the cows in the treatment group tended to have shorter intervals from calving to first insemination compared with cows in control group. The pregnancy rate to first service for cows treated with PG was 2.50 times greater compared with cows in control group. The energy balance was less negative for treatment group compared with control cows. In conclusion, although, drenching with 250 mL of PG per day from 3 to 15 days after calving did not improve the onset of luteal activity postpartum, treated cows tended to have shorter intervals from calving until first service. Propylene glycol administration would improve the negative energy balance status as observed by serum BHBA concentration, which might be an advantage to increase pregnancy rate at first AI in dairy cows experiencing seasonal heat stress.
Keywords: Cow; Fertility; Postpartum period; Pregnancy; Propylene glycol